FENOMENA DAN PENANGANAN BULLYING PADA SISWA SOFT MASCULINITY - Ahmad Reza Samamang; Nur Fadhilah Umar; Zulfikri; Nurfaidah Ardis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the phenomenon of soft masculinity in male students which is often perceived as different from traditional masculinity constructions so that they are vulnerable to being targeted by bullying in the school environment. These conditions can cause various psychological, social, and academic impacts that hinder the development of students. This study aims to describe the phenomenon of soft masculinity, the form of bullying experienced, the factors causing and impact, as well as efforts to handle it through individual counseling services for students at SMAN 10 Jeneponto. The research uses a qualitative approach with a case study type on one student with the initials MAI. Data collection is carried out through in-depth interviews, observations, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The validity of the data was tested using source triangulation and triangulation techniques. The results of the study showed that the subjects experienced verbal, relational, and cyberbullying in the form of ridicule, negative nicknames, social exclusion, and derogatory comments on social media. Bullying behavior is influenced by gender stereotypes, patriarchal culture, and peer pressure on masculinity standards. The impacts experienced include low self-confidence, anxiety, shyness, difficulty interacting socially, and decreased study concentration. Treatment through individual counseling services using the Cognitive Behavioral Therapy (CBT) approach with assertive training techniques has been proven to help subjects change negative mindsets, increase assertive behavior, build confidence, and develop the ability to deal with bullying more adaptively. The findings of this study show that CBT-based individual counseling services with assertive training techniques are effective in helping students cope with bullying and improve self-adjustment in the school environment.